2014
DOI: 10.14444/1022
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Foraminal Decompression for Failed Back Surgery Syndrome under local Anesthesia

Abstract: BackgroundThe most common causes of failed back surgery are residual or recurrent herniation, foraminal fibrosis and foraminal stenosis that is ignored, untreated, or undertreated. Residual back ache may also be from facetal causes or denervation and scarring of the paraspinal muscles.1–6 The original surgeon may advise his patient that nothing more can be done on the basis of his opinion that the nerve was visually decompressed by the original surgery, supported by improved post-op imaging and follow-up studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 23 publications
1
70
1
Order By: Relevance
“…The elderly often have comorbidities (32) rendering them at high risk for general anesthesia, so surgeries that can be done under local anesthesia are preferable in this age group. However, based on anatomic considerations, only the TF approach for foraminal stenosis has been discussed in the literature (14)(15)(16)(17). In practice, during foraminoplasty via the TF approach, we have sometimes noticed that the traversing nerve root is decompressed at the same time as the exiting nerve, due to wide removal of the superior facet joint on the cranial side ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly often have comorbidities (32) rendering them at high risk for general anesthesia, so surgeries that can be done under local anesthesia are preferable in this age group. However, based on anatomic considerations, only the TF approach for foraminal stenosis has been discussed in the literature (14)(15)(16)(17). In practice, during foraminoplasty via the TF approach, we have sometimes noticed that the traversing nerve root is decompressed at the same time as the exiting nerve, due to wide removal of the superior facet joint on the cranial side ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In a report underscoring the importance of foraminal stenosis as a cause of residual symptoms in patients with failed back surgery, Yeung and Gore described 30 patients treated with TF-PED technique in whom foraminoplasty could be performed under local anesthesia (14). The mean visual analog score in these patients improved from 7.2 preoperatively to 4.0 postoperatively and the Oswestry Disability Index from 48% to 31%.…”
Section: Decompression Surgery Using Tf-pedmentioning
confidence: 99%
“…Some surgeons prefer the percutaneous endoscopic approach for HNP in cases involving high‐grade migration, and good results have been obtained . Yeung and Gore suggested that HNP in the hidden zone can be safely accessed by transforaminal PELD . Ahn et al reported a standardized technique of transforaminal PELD for very high‐grade migrated disc herniation; they obtained excellent or good global outcomes in 84.6% of patients, and the rate of symptomatic improvement was 92.3% .…”
Section: Discussionmentioning
confidence: 99%
“…The best method at this time is to distribute information in open access journals and training efforts. Clinical research can still be validated with traditional EBM methods of validation as long as they are also peer reviewed by qualified reviewers [6][7][8]. The treatment algorithm in spine is evolving and changing due to a better understanding of the patho-anatomy, well correlated with its pathophysiology.…”
Section: Transforaminal Endoscopic Decompression and Intradiscal Therapymentioning
confidence: 99%